Charge coupled device based on optical tomography system in detecting air bubbles in crystal clear water - Juliza Jamaludin; Rahim, RA; Rahim, HA; Rahiman, MHF; Muji, SZM; Rohani, JM (Elsevier Sci Ltd, 2024)
Optical tomography is one of the tomography methods which are non-invasive and non-intrusive system, consisting of emitter with detectors. Most of the available detectors systems are intrusive where sensors or probes need to be placed within the analyzed processes and this will create disturbances in the current processes. This research are conducted in order to analyze and proved the capability of laser with Charge Coupled Device in an optical tomography system for detecting air bubbles exist in crystal clear water. Experiments in detecting moving air bubbles are conducted. The images of captured data are reconstructed based on filtered image of Linear Back Projection with Hybrid algorithms. As a conclusion, this research have successfully developed an optical tomography system that capable to capture the image and measure the diameter and velocity of rising air bubbles in a non-flowing crystal clear water. (C) 2016 Elsevier Ltd. All rights reserved.